N-terminal half of MED14 is critical for Mediator-RNA polymerase II interaction and the resulting transcription - Baris, Yasemin; Jabbar, Javaid; Yozgat, Yasemin; Dinccelik-Aslan, Melike; Cigirgan, Ege; Erden, Merve; Bay, Sadik; Aslan, Volkan; Cevher, Murat Alper (The journal of biological chemistry, 2025)
Mediator is a large and evolutionarily conserved coactivator complex essential for RNA polymerase II (Pol II)-mediated gene regulation at multiple steps of the transcription process, including preinitiation complex assembly and function. Here, we used the MultiBac baculovirus expression system to generate recombinant human core Mediator subcomplexes and subsequent biochemical approaches to dissect the mechanism by which Mediator facilitates recruitment of Pol II to core promoters. Our results highlight a pivotal role in this process for the N-terminal half of the MED14 (MED14-NTD) subunit. We show that a reconstituted 15-subunit human core Mediator complex that contains only the MED14- NTD is fully functional in facilitating both basal and activated (p53) transcription. This complex directly interacts with the RPB1 subunit of Pol II and is required for recruiting Pol II to core promoters. LC-MS/MS analysis of Mediator-bound RPB1 indicates that the CTD is predominantly hypophosphorylated (≤1% detectable Ser5-P), consistent with recruitment-stage engagement. Moreover, recombinant RPB1 can completely reverse the human core Mediator-Pol II interaction. Notably, the human MED14-NTD region has secondary structure conservation with Schizosaccharomyces pombe. In addition, reanalysis of published cryo-EM structures of yeast Mediator-Pol II complexes strongly supports our conclusion. Thus, our analyses provide critical new insights into how Mediator binds to Pol II and recruits it to the promoters to facilitate transcription.
Online verfügbar: 17. Oktober 2025, Artikelversion: 1. Dezember 2025
Gesehen am 27.02.2026